Analysis of the Production Concept in the Thought of Muhammad Baqir Shadr and Its Relation to Conventional Economics - Muhammad Maulana Darsono; Yadi Janwari; Ahmad Hasan Ridwan (International Economic and Finance Review, 2023)
This research aims to present the model of creation based on Baqir Shadr, as well as Baqir Shadr's critical analysis of the creation style of capitalism. The research is carried out using literature or library research that examines the concept of creation based on Baqir Shadr's thoughts with some literature and literature related to the research topic. The results of the study show that the things that make the concept of creation of capitalism, socialism, and Islam different are caused by the motives of the actors in this case the producer in achieving his goals which are influenced by the economic doctrine he adheres to. To increase the creation of up to there are 2 facilities that can be taken, namely intellectual facilities as a paradigm that is used as a way of life for each producer so that it will shape his ethics and morality in production. Next is the legal facility which is a facility positioned as a provision in the creation which consists of maximizing the use of land into productive land and eliminating the application of usury in creation where the use of interest is included in the instrument. Meanwhile, Baqir Shadr's critical analysis of the concept of capitalism creation is that if the highest profit is the target, it means that the matter makes the position of creation only based on demand which is influenced by purchasing energy. There is also a large purchasing energy that is only owned by a certain group, making the poor have no influence on the economy.   Keywords: Initiating, Model, Production,                       Baqir Shadr